The diversity of fungal associates of Dendrobium ovatum (L.) Kraenzl., an endemic orchid of the Western Ghats of India (Universitas Gadjah Mada, 2024)
Dendrobium ovatum is a tropical epiphytic orchid endemic to the Western Ghats of India and has been listed as a threatened species in recent research due to its declining populations and changes in flowering and fruit set patterns. This study aims to investigate the mycoflora associated with the roots, stems and leaves of D. ovatum. Both surface‐associated and endophytic fungal associates were isolated and identified using morphological and molecular methods. The study resulted in the isolation of 139 cultures, which were divided into 24 morphotypes, 99% of which belonged to Ascomycota. The most dominant members, Trichoderma harzianum and Colletotrichum gloeosporioides, were consistently observed across all the study sites. Tissue‐specific fungal diversity analysis revealed that each organ was dominated by a distinct fungal group, forming characteristic communities specific to each tissue. The roots of D. ovatum exhibited the highest species richness and diversity, compared to the stem and leaves. This research also represents the first documentation of fungal associates of the threatened orchid D. ovatum.